A Labour Party View - Caygill, David (Victoria University of Wellington Law Review, 1995)
David Caygill, the then-Deputy Leader of the Opposition, explores the Treaty of Waitangi settlement process from the perspective of the Labour Party. First, the author and his party reject the fiscal envelope to address outstanding Treaty claims. Secondly, the author discusses outstanding Article II claims under the Treaty. Finally, the author also discusses Article III claims. The author concludes that the real unfinished business is less about settlement and more about giving the Treaty contemporary meaning.